Determination of Lead(II) in Milk by Flame Atomic Absorption Spectrometry after Solid Phase Extraction - Tohidifar, Hosna; Moghimi, Ali; Ayvazzadeh, Orang; Eskandari, Sohil (Asian Journal of Chemistry, 2013)
A simple and selective solid phase extraction method for determination of lead in milk and arouses solutions has been reported. The method is based on the adsorption of lead on octadecyl bonded silica cartridges (C18) modified by sodium dodecyl sulfate and 1-(2-pyridylazo)-2-naphthol. The influence of acidity, eluting agents, stability of the column, sample volume and interfering ions has been investigated. The adsorbed complex could be eluted using environmentally benign 5 mL of 1 mol L-1 HNO3 and the concentration of lead(II) was determined by flame atomic absorption spectrometry. A detection limit of 0.050 μg L-1 could be achieved and the developed procedure was successfully applied for the determination of lead(II) in tap water and milk samples. Precision at 1 mg L-1 was 1.44 % (n = 5).